Practices and knowledge in public higher education in the Bahia Recôncavo - Francisca Helena Marques; Jorge Luis Ribeiro de Vasconcelos; Sólon Mendes (Universidade Federal do Norte do Tocantins, 2021)
In this article we will present three excerpts of the activities related to the Centro de Cultura, Linguagens e Tecnologias Aplicadas (CECULT/UFRB), through the performance of three professors of this Center (Francisca Helena Marques, Jorge Luiz Ribeiro de Vasconcelos and Solon de Albuquerque Mendes). All the activities have in common the concern for the process of bringing public higher education to the interior of the country and the insertion of knowledge from the rural environment, articulated through teaching, research and extension. It is noteworthy that CECULT has many students from rural communities in the municipalities of Recôncavo Baiano, and it is appropriate to deepen these practices and exchanges of knowledge that occur in the process of internalization of public higher education. We adopt a mixed methodological approach, involving aspects of experimental, bibliographical, phenomenological, qualitative, quantitative research. Regarding the results, we can observe more closely the profile of four students, and through this, build a more dialogic relationship between educators and students.